Framework for Numeracy and Digital Skills Attributes in Higher Education - Siti Fairuz Dalim; Sharipah Ruzaina Syed Aris; Teoh Sian Hoon; Fazyudi Ahmad Nadzri; Sayang Mohd Deni; Norasikin Yahya; Ellianawati M. Si (Research in Social Sciences and Technology- OpenED Network, 2023)
Numeracy and digital skills are among the most crucial skills that any graduate should possess before entering the workforce, regardless of their field of study. Therefore, both skills should not be treated as an “add on” skill but viewed as essential graduate attributes needing to be purposefully incorporated into the curriculum instead of mere chance. By understanding the learners’ numeracy and digital skills abilities, educators can create suitable learning outcomes, activities, and assessments, enabling them to acquire the skills. The objective of this study is to create a framework for testing numeracy (NSI) and digital skills (DSI) using a cross-sectional design and quantitative methodology. The research entails generating a questionnaire, verifying it via a rigorous procedure of expert content validation, and focusing on sufficiency, clarity, coherence, and relevance. A pilot study involving 218 students from various disciplines was conducted to measure the reliability of the framework using Cronbach Alpha. Feedback from experts was then used to enhance the questionnaire, resulting in the finalisation of five components for the Digital Skills Instrument (DSI): information literacy, computer and technology literacy, digital communication and collaboration skills, digital identity and well-being, and digital ethics. Meanwhile, the five components of the Numeracy Skills Instrument (NSI) encompassed operation and calculation, graphical representation, quantitative reasoning and logical thinking, complex number (advanced concept), spatial visualisation and geometric reasoning. The results indicated a strong internal consistency across all components for both tools, with alpha values ranging from 0.847 to 0.958 for DSI and 0.916 to 0.964 for NSI. Corrected item-total correlations also depicted intercorrelation between items for both instruments. To sum up, the findings demonstrate that the DSI and NSI have high reliability and validity. Because both tools are reliable and valid for measuring digital and numeracy skills in the Malaysian context, they can be confidently used for future research.